Hubungan Pengetahuan Orang Tua Dengan Pencegahan Diare Pada Balita Di Puskesmas Kampung Delima - Ulfah, Sofia Maria; Umami, Desi Aulia; Putri, Yesi (Utami Publisher, 2025)
In the Kampung Delima Health Center area, the incidence of diarrhea is quite high, with one toddler dying due to recurring diarrhea in a village within the health center's working area. Initial interviews with the diarrhea program officer revealed that medical actions from early symptoms to hospital referral had been conducted. However, audit results showed that family factors, such as economic conditions and knowledge, contributed to the patient's worsening condition and eventual death. This study aims to determine the relationship between knowledge about diarrhea and parental behavior in preventing diarrhea in toddlers in the Kampung Delima Health Center area. This research employs a quantitative design with a cross-sectional approach. The sample size consists of 50 participants, and data collection was conducted using a questionnaire. The results of the Chi-Square test indicate a significant relationship between knowledge of diarrhea and parental behavior in preventing diarrhea, with a p-value of 0.012 (p < 0.05). Based on the research findings, the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. In conclusion, knowledge about diarrhea is significantly related to prevention behaviors. It is recommended that the Kampung Delima Health Center develop continuous educational programs, hold regular outreach activities, provide adequate facilities, and conduct routine monitoring and evaluation.